2011
DOI: 10.1186/1471-2202-12-128
|View full text |Cite
|
Sign up to set email alerts
|

It's not what you say but the way that you say it: an fMRI study of differential lexical and non-lexical prosodic pitch processing

Abstract: BackgroundThis study aims to identify the neural substrate involved in prosodic pitch processing. Functional magnetic resonance imaging was used to test the premise that prosody pitch processing is primarily subserved by the right cortical hemisphere.Two experimental paradigms were used, firstly pairs of spoken sentences, where the only variation was a single internal phrase pitch change, and secondly, a matched condition utilizing pitch changes within analogous tone-sequence phrases. This removed the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Repetitive TMS (rTMS) can be applied as either low (≤1 Hz) or high (≥5 Hz) frequency; the former considered typically inhibitory to underlying neurons, the latter excitatory (Pell et al 2011). The effects on distal but functionally connected regions may be more complex (Tracy et al 2011, Tracy et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Repetitive TMS (rTMS) can be applied as either low (≤1 Hz) or high (≥5 Hz) frequency; the former considered typically inhibitory to underlying neurons, the latter excitatory (Pell et al 2011). The effects on distal but functionally connected regions may be more complex (Tracy et al 2011, Tracy et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the role of the right-hemisphere in acoustic processing of lexical tones that is important for spoken Mandarin, there is evidence that phonological processing of lexical tones is subserved by the left hemisphere in native Mandarin speakers (Gandour et al, 2004;Gu, Zhang, Hu, & Zhao, 2013;Tracy et al, 2011;Wang, Wang, & Chen, 2013;Xu et al, 2006). Electrophysiological and fMRI evidence has shown that processing lexical tones is left-lateralized in native Mandarin speakers, especially for pitch contour information, while processing acoustic tones remains right-lateralized regardless of listeners' language background (Gandour et al, 2004;Tong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…How a speaker says something is as relevant as what he or she says (Tracy et al, 2011). In all of these situations, the verbal message is important, but so is the nonverbal language, which supports the meaning of the message.…”
mentioning
confidence: 99%
“…In all of these situations, the verbal message is important, but so is the nonverbal language, which supports the meaning of the message. How a speaker says something is as relevant as what he or she says (Tracy et al, 2011).…”
mentioning
confidence: 99%